Recent Progress of Membrane Distillation Technology Applied in Desalination - Chen Xi (E3S Web of Conferences, 2019)
Membrane distillation (MD), as a biphasic separation method, has promising application prospect in seawater and brackish water desalination with desirable properties such as low energy consumption, cost-effective and high salt rejection, which has attracted more attention from researchers to explore its potential. In this paper, we summarize the operating mechanism and typical configurations of MD. Recent advances in three main research directions, including reforming membrane material, optimizing separation process and changing power source, are briefly overviewed. Additionally, challenges of future studies in MD are discussed at the end of this review, which purports to provide a reference for further development.